THE CONTRASTING VOICES OF PSALM 95 - Savran, George W. (Revue biblique, 2003)
Psalm 95 is characterized by a division into two parts which differ sharply in tone, content, and speaker. Working with the tools of literary analysis this article argues for the integrity of the psalm. The second half of the psalm challenges the claims of piety and obedience in the first part point for point, in order to question the sincerity of these declarations in light of a unique reading of the wilderness traditions. Le psaume 95 se caractérise par une division en deux parties, qui diffèrent fortement quant aux ton, contenu et locuteur. Utilisant les outils de l'analyse littéraire, cet article tient pour l'unicité du psaume. La seconde partie met en cause point par point les appels à la piété et à l'obéissance de la première partie, pour en vérifier la sincérité, à la lumière d'une lecture unique des traditions du désert.